The exploration of the internal homogeneities for a LiFePO4 pouch lithium-ion battery with a 3D electrochemical-thermal coupled model - Jianpeng Mi; Xiaolong Liu; Daiman Zhu; Longfei Chen; Yongli Li (Next Energy, 2024)
Along with the battery charge/discharge processes, the migration of the Li ions inevitably leads to an inhomogeneous distribution of the battery internal electrochemical and thermal characteristics, deteriorating the battery capacity and safety. In this work, the internal characteristics of a 20 Ah pouch LiFePO4 lithium-ion battery have been investigated based on a 3D electrochemical-thermal coupled model. It is found that the reduction of the particle size for either the cathode or anode would increase the battery capacity. Moreover, with the modulation of the thickness of cathode (Lpos) and convective heat transfer coefficient (h), the homogeneity of solid lithium concentration and temperature has been optimized. A relatively smaller Lpos and an h higher than the critical value should be adopted. From the aspect of thermal distribution, as the discharge rate increases, the irreversible reaction heat always dominates, while the proportion of ohmic heat among the total heat increases, and the high temperature region always locates on the inner sides of the tabs. The methodology proposed in this work could be applied to pouch batteries with more repeated cell units and larger sizes.